After Brexit: Which Country is Next? Array - Gonpot, Preethee Nunkoo (Acta Universitatis Danubius. Relationes Internationales, 2021)
Objective: In this paper, we investigate any next potential exit from the European Union after Brexit which has left a distinct scent of a withering Europe in the air. Prior Work: Most analyses have concentrated why Brexit and the effect on Britain rather than the remaining countries in the EU. Approach The thinking is: Can there be a domino effect? The methodological approach is based on the optimum currency area theory. The study focuses on the economic convergence criterion and a four variable structural vector autoregression model is used to recover the four underlying shocks: domestic demand, domestic supply, external supply, and monetary shocks. Results The correlation analysis of the shocks support Brexit and point out unanimously Sweden to be the next most likely to exit from EU given that its shocks’ follow a similar pattern to that of the UK. Even though not as imminent as Sweden, Poland’s shocks show enough asymmetric trait with the region, for it to be an exit contender. Implications There is a possibility of a new wave of “de-europeanisation” if UK succeeds and political will is one such factor that may trigger other potential waverers. Value This paper brings in another dimension to the Brexit conundrum and brings in the thought provoking idea of looking at what may happens if Brexit is successful.